The Role of Natural Gas in the EU Decarbonisation Path - Manfred Hafner; Simone Tagliapietra (Fondazione Eni Enrico Mattei (FEEM), 2015)
Over the last decade decarbonisation has become a key priority for the EU. However, on the contrary of renewable energy or energy efficiency, the role of gas in this process has never been clearly defined. This uncertainty opens a wide debate on the future role of gas in the EU energy system, particularly vis-à-vis the progressively stronger role of renewables in the EU energy mix. This paper tackles this issue with the aim to explore what role gas might play in making the EU decarbonisation path more balanced and secure up to 2030 and beyond.
Keywords: Q40; Q42; Q48; 330; Gas; Decarbonisation; EU Energy Policy